Reflections on Hemingway’s Life Experience in A Farewell to Arms (Historical-Biographical Study) - Everhard Markiano Solissa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research is to find and describe the relationship between Hemingway’s life story in A Farewell to Arms and his real life. This research is a qualitative descriptive study with a historical-biographical approach, that is, an approach that sees literature as the life and era of its author. The research data is in the form of novel texts that describe the characters and the setting of the place. The data were obtained by using the reading-note technique, namely reading the data carefully and recording the parts of the data related to the setting, characters, and characterizations. The data were analyzed by describing the setting and characters in A Farewell to Arms then compared with the data on The German Wars 1914–194, World War I and http://id.wikipedia.org/wiki/Ernest_Hemingway. The results of the analysis show that there is a relationship between the character and place in A Farewell to Arms and the author’s life.